LINGUISTICS IS THE SCIENTIFIC STUDY OF HUMAN LANGUAGE (Conference Zone, 2022)
Linguistics may be characterized as the logical ponder of dialect. This definition, unexceptionable as distant because it goes, is one that will be found in a huge number of reading material and well-known presentations to the subject.